Ring-opening polymerisation of l- and rac-lactide using group 4 permethylpentalene aryloxides and alkoxides - Turner, ZR; Lamb, JV; Robinson, TP; Mandal, D; Buffet, J-C; O'Hare, D (Royal Society of Chemistry, 2021)
A new family of group 4 permethylpentalene (C8Me62−; Pn*) aryloxide and alkoxide complexes have been synthesised and fully characterised by multinuclear NMR spectroscopy and single-crystal X-ray diffraction; (η8-C8Me6)Zr(OR)2 (R = tBu (1), 2,6-Me-C6H3 (2), 2,6-iPr-C6H3 (3) and 4-OMe-C6H4 (4)), (η8-C8Me6)Zr (OR) (R = 2,6-tBu-C6H3 (5) and 2,6-tBu-4-Me-C6H2 (6)), (η8-C8Me6)ZrCp(OR) (R = tBu (7), 2,6-Me-C6H3 (8) and 2,6-iPr-C6H3 (9)), (η8-C8Me6)TiCp(O-2,6-Me-C6H3) (10) and (η8-C8Me6)ZrCpMe(OR) (R = 2,6-Me-C6H3 (11), 2,6-iPr-C6H3 (12) and 2,4-tBu-C6H3 (13)). 2, 3, 6, 7, 9, 10 and 12 were studied as initiators for the ring-opening polymerisation (ROP) of L-lactide, and 2, 3, 6, 7 and 10 were studied as initiators for the ROP of rac-lactide. 3 was found to be the most active initiator for the ROP of L-lactide (kobs = 0.35 h−1) and 2 for the ROP of rac-lactide (kobs = 0.21 h−1). These initiators produced isotactic PLA for the ROP of L-lactide and moderately heterotactic enriched (maximum Pr of 0.69) or atactic PLA for the ROP of rac-lactide with polymer chains consisting of polylactic acid repeat units with –OR and –OH end groups.